2015
DOI: 10.1515/revecp-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Regional Railway Transport in Czech, Austrian and German Decentralised and Regionalised Transport Markets1

Abstract: The article analyses railway transport markets in three neighbouring Central European countries: the Czech Republic, Austria and Germany (specifically Bavaria and Saxony), with a focus on regional transportation. It examines the organisational form of public transport resulting from regionalisation and provides comparative case studies of regional train services in these countries. The article points out the organisational differences in public transportation between the studied regions and tries to connect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…For the purposes of this research, time distance of train travel from the selected point in the centre was selected as the most appropri-ate. Similarly, the region was delineated by Seidenglanz et al (2014), and Seidenglanz et al (2015). J. Dujka (2014) uses the same procedure in a modified form.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purposes of this research, time distance of train travel from the selected point in the centre was selected as the most appropri-ate. Similarly, the region was delineated by Seidenglanz et al (2014), and Seidenglanz et al (2015). J. Dujka (2014) uses the same procedure in a modified form.…”
Section: Methodsmentioning
confidence: 99%
“…1 The significance of the Brno urban region is not negligible in the settlement structure of the Region and the entire Czech Republic. The Brno urban region is not defined in a uniform manner or administrative delimitation; however, a number of research works have attempted to define it, among others Atelier Era 2008, Hampl (1996Hampl ( , 2005, Mulíček et al (2006), Mulíček and Szczyrba (2004), Seidenglanz et al (2014), Seidenglanz et al (2015).…”
Section: Brno Urban Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combustion of lignite causes the greatest greenhouse gas emission. In order to reduce emissions, the German government launched a process that will reduce carbon consumption in the country [17].…”
Section: Research Proceduresmentioning
confidence: 99%
“…(Skrúcaný et al, 2016) who studied the environmental burden caused with road and railway regional transport on the basis of simulating the fuel consumption of a bus and a train on Žilina -Rajec line with a certain amount of passengers. Seidenglanz et al referred to a diversified organisation of regional public transport in three neighbouring Central European countries: the Czech Republic, Austria and Germany (Seidenglanz et al, 2015). Guihéry considered costs structure of operating regional railway passenger transport before and after competition and showed that the introduction of competition in Leipzig region had reduced the level of subsidy by 20 %, and improved productivity of the incumbent operator (Guihéry, 2014).…”
Section: Introductionmentioning
confidence: 99%